(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to develop a context-based digital comic video as an English for Specific Purposes (ESP) learning medium to improve the speaking skills of eleventh-grade students in the Tourism Expertise Program at SMK TP 45 Negara, Bali. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through a needs analysis questionnaire, expert validation sheets, teacher response questionnaires, and student practicality questionnaires. Data were analyzed using descriptive percentage statistics to determine the level of validity and practicality of the product, while content validity was analyzed using the Gregory coefficient. The results of the study indicate that the developed media is in accordance with the needs of ESP learning because it integrates the local tourism context of Jembrana into English speaking materials. The results of expert validation indicate that the media has a very high level of validity, both in terms of material and design. In addition, the results of the practicality test indicate that the media is easy to use and receives positive responses from both teachers and students. These findings indicate that the context-based digital comic video is suitable for use as an ESP learning medium and has the potential to support the development of students’ speaking skills in the tourism expertise program